2011
DOI: 10.1090/s1061-0022-2011-01179-3
|View full text |Cite
|
Sign up to set email alerts
|

On the problem of time-harmonic water waves in the presence of a freely floating structure

Abstract: Abstract. The two-dimensional problem of time-harmonic water waves in the presence of a freely floating structure (it consists of a finite number of infinitely long surface-piercing cylinders connected above the water surface) is considered. The coupled spectral boundary value problem modeling the small-amplitude motion of this mechanical system involves the spectral parameter, the frequency of oscillations, which appears in the boundary conditions as well as in the equations governing the structure's motion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 11 publications
1
26
0
1
Order By: Relevance
“…In order to obtain a family of immersed parts of motionless bodies that trap waves in the water covered by the brash ice we follow the considerations used in § § 3 and 4 of Kuznetsov (2011) with ν changed to ν (σ ) = ν/(1 − νσ ).…”
Section: Construction Of a Family Of Motionless Trapping Bodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to obtain a family of immersed parts of motionless bodies that trap waves in the water covered by the brash ice we follow the considerations used in § § 3 and 4 of Kuznetsov (2011) with ν changed to ν (σ ) = ν/(1 − νσ ).…”
Section: Construction Of a Family Of Motionless Trapping Bodiesmentioning
confidence: 99%
“…It should be mentioned that the same semi-inverse procedure was used by Kuznetsov (2011) for obtaining two-dimensional trapping bodies that are motionless in the open water. However, there is an essential distinction between the case of open water and water covered by brash ice, namely no restriction was imposed on the trapping frequencies in the former case.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of such modes was later demonstrated for freely floating bodies constrained to move in heave (McIver & McIver 2006;Fitzgerald & McIver 2010). More recently, the existence of these modes in the floating-body problem was rigorously proved by Kuznetsov (2011) and Kuznetsov & Motygin (2012 without restrictions on the mode of body motion. Trapped modes are mainly of theoretical importance since they prove non-uniqueness in the water wave problem.…”
Section: Introductionmentioning
confidence: 98%
“…In 1950, John proved that the solution to the radiation problem is unique if the frequency of the harmonic motion is large enough and the freely floating object satisfies a certain geometrical condition (no point of the immersed surface lies below a point of the free surface). Since then, the problem of trapping of water waves by freely floating structures has rarely been considered in full generality, notable exceptions being the articles of Beale (1977), who studied the corresponding initial-value problem, and Kuznetsov (2010), who considered the two-dimensional problem and observed that motionless freely floating structures support trapped mode solutions. In most recent work, attention has been either restricted to the two-dimensional case (McIver & McIver 2006;Evans & Porter 2007;Porter & Evans 2009) or the motion of the floating structure constrained to heaving motion Newman 2008;Porter & Evans 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a reduction scheme in the form of a suitable trace operator (cf. Nazarov 2008) has led to a series of simple sufficient conditions guaranteeing the existence of trapped modes around fixed structures in different geometrical configurations (see Nazarov 2009a-c;Nazarov & Videman 2009, 2010.…”
Section: Introductionmentioning
confidence: 99%